The Role of Gender as A Moderating Variable of Satisfaction with Local Brand Clothing Towards Customer Loyalty in Generation Z - Nadhila Ichsan; Miqdad Ihkamuddin; Diah Karmiyati (Yayasan Adra Karima Hubbi, 2024)
This study aims to examine the role of gender in moderating the influence of customer satisfaction on customer loyalty in generation Z who use local brand clothing in Indonesia. The subjects of the study were 40 respondents with an age range of generation Z (born 1995-2010) who had purchased local brand clothing. Data were collected using the accidental sampling method and processed using the moderation regression technique. The results showed that gender acts as a moderator that influences the relationship between customer satisfaction and loyalty. The influence of satisfaction on loyalty is greater in men than in women. This shows that men are more likely to increase or strengthen loyalty based on rational satisfaction with product quality, while women are influenced by emotional factors and long-term relationships. These findings support the importance of considering gender differences in marketing strategies to increase customer loyalty.